Opportunities and challenges of digital twins in structural health monitoring - Tran, Minh Quang (2024)
Digital twin (DT) is one of the most modern and promising technologies in realizing smart manufacturing and implementing Industry 4.0. DT offers opportunity to integrate the physical world with digital world with a seamless data source. Civil engineering industry, in general, is facing many challenges in the process of digital transformation to improve efficiency and technology to meet the current growth rate of the economy. DT technology has the potential to transform and improve the exploitation and management of infrastructure in civil engineering, especially in the service phase. Based on DT model, managers and maintenance operators can test different scenarios, improve efficiency, and make accurate decisions in maintenance of the structure, leading to reduction of management and other regular monitoring costs, as well as accurate prediction of risks during the lifespan of the infrastructure. This study presents advances in digital twin implementations in structural health monitoring. This presents the opportunities and challenges of the digital twin in structural health monitoring with current technologies and future directions.